Harvard business review on leadership (Harvard Business School P. BostonUS, 1998)
Presents leadership and management as two distinctive and complementary systems of action, each with its own function and characteristic activities. Examines topics including: the discipline of building character; and, the human interaction aspect of management. Suggests that today's business leaders need to reclaim managerial responibility.
Located in the Learning Resource Centre